Pemasaran Padi Organik - Raharja, I Made Dwicky; Arisena, Gede Mekse Korri (Jurnal Nasional Manajemen Pemasaran dan SDM, 2025)
Organic rice is increasingly in demand, especially due to the impact of COVID-19, which has increased public awareness of health and raised more concern for the environment. This organic rice also functions to maintain a country's food security and has nutritional content that is free from synthetic chemicals, making it good for health. Although the market prospects for organic rice are quite promising, the marketing process still faces various challenges, such as price fluctuations, limited market access, and a lack of understanding from farmers regarding effective marketing strategies, which are obstacles in expanding the organic rice market. In addition, the large price difference between producers (farmers) and each marketing chain causes farmers' profits to be less than optimal and can reduce consumer interest. Therefore, a study is needed on the effectiveness of marketing channels and strategies that can increase the competitiveness of organic rice products in the market. This study aims to analyze the margins in organic rice marketing channels, as well as to analyze their efficiency. The method used in this study is the library research method (literature study). The results of the survey indicate that relatively high selling prices still constrain organic rice marketing due to inefficient marketing channels and limited distribution networks to the market. Therefore, strategies for marketing channels and determining the right partnerships are needed to increase organic rice marketing. Additionally, the government needs to support market access, provide incentives for farmers, and expand education about the importance of organic products. With a more effective marketing strategy, it is hoped that organic rice can achieve higher competitiveness in both domestic and international markets.